Developing a PMRI-based augmented reality learning trajectory to support students’ problem-solving skills in circle geometry - Trisna Wulandari; Ely Susanti; Cecil Hiltrimartin (Universitas Hamzanwadi, 2026)
This study reports a validation study within design research aimed at developing a PMRI-based augmented reality (AR) learning trajectory to support high school students’ problem-solving skills in circle geometry. The subjects of this study were 35 eleventh-grade students at a senior high school in Palembang. The research employed a design research methodology, specifically a validation study, consisting of three phases: preliminary design, design experiment, and retrospective analysis. Data were collected from worksheets, classroom observations, and problem-solving tests, and analyzed descriptively using qualitative and quantitative approaches. This study produced a learning trajectory consisting of a sequence of contextual and AR-assisted learning activities that guided students from exploring real-world circular situations to formal circle concepts. The implementation of this trajectory resulted in measurable improvements in students’ problem-solving skills, as indicated by an increase in mean test scores from 19.37 in the pre-test to 66.51 in the post-test. Students demonstrated strong performance in understanding problems, devising solution plans, and carrying out solution strategies, with achievement percentages ranging from 71% to 100% on these indicators. However, students’ evaluation and reflection skills remained relatively low, indicating the need for greater emphasis on reflective activities within the learning trajectory.